Analisis Dan Perancangan Sistem Pendukung Keputusan Penerima Bantuan Pangan Non Tunai (BPNT) Dengan Simple Additive Weighting (SAW) Pada Dinas Sosial Kota Jambi - Riyansuni, Iper; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2020)
Dinas Sosial (DINSOS) of Jambi City is one of the Technical Offices in the Jambi City Government whichholds the authority of the Social Affairs government affairs. One of them is the handling of the poor, theprogram of Dinas Sosial Jambi City, namely Non-World Food Aid, which aims to help the community byproviding food assistance such as eggs and rice. But in the program there were obstacles faced indetermining BPNT recipient residents, there were still poor people who had not been verified and validatedwhether the population really included poor people who were eligible to receive BPNT. To overcome this, theauthor tries to analyze and design a prototype of the decision support for Bantuan Pangan Non TunaiRecipients (BPNT) with Simple Additive Weighting (SAW). With this research, it is hoped that later it will beable to overcome existing problems and the poor get their rights